Rancang Bangun Purwarupa Pengaturan Lampu Lalu Lintas Berdasarkan Kepadatan Arus Kendaraan Berbasis Mikrokontroler ATMega 328P - I Irfan; Diyah Ruri Irawati; Yudi Irawan Chandra; Marti Riastuti (LPPM STIKOM Tunas Bangsa, 2024)
Efficient and adaptive traffic light management is becoming increasingly important in the midst of rapid urban growth. This research aims to design and implement a prototype ATMega 328P microcontroller-based traffic light management system that is responsive to vehicle flow density. The ATMega 328P microcontroller was chosen for its robust and efficient ability to process real-time information. The research methodology involves analyzing the density of vehicle flow on a roadway and developing a traffic light setting algorithm that can automatically adjust the duration of the lights according to changing traffic conditions. The system is equipped with various sensors, such as vehicle presence sensors and traffic density sensors, to accurately detect and monitor traffic conditions. The prototype was tested in simulation and field experiments to evaluate its performance in optimizing traffic flow. The results show that the system is capable of improving traffic efficiency by reducing waiting time at intersections, reducing traffic congestion, and overall improving vehicle mobility. In addition, this implementation has the potential to reduce exhaust emissions and contribution to air pollution due to better vehicle movement efficiency. By utilizing microcontroller and sensor technology, these adaptive traffic light settings can be integrated in intelligent transportation systems to create more sustainable and environmentally friendly cities.